Reprogramming mechanism dissection and trophoblast replacement application in monkey somatic cell nuclear transfer - Zhaodi Liao; Jixiang Zhang; Shiyu Sun; Yuzhuo Li; Yuting Xu; Chunyang Li; Jing Cao; Yanhong Nie; Zhuoyue Niu; Jingwen Liu; Falong Lu; Zhen Liu; et al. (Nature Communications, 2024)
Abstract Somatic cell nuclear transfer (SCNT) successfully clones cynomolgus monkeys, but the efficiency remains low due to a limited understanding of the reprogramming mechanism. Notably, no rhesus monkey has been cloned through SCNT so far. Our study conducts a comparative analysis of multi-omics datasets, comparing embryos resulting from intracytoplasmic sperm injection (ICSI) with those from SCNT. Our findings reveal a widespread decrease in DNA methylation and the loss of imprinting in maternally imprinted genes within SCNT monkey blastocysts. This loss of imprinting persists in SCNT embryos cultured in-vitro until E17 and in full-term SCNT placentas. Additionally, histological examination of SCNT placentas shows noticeable hyperplasia and calcification. To address these defects, we develop a trophoblast replacement method, ultimately leading to the successful cloning of a healthy male rhesus monkey. These discoveries provide valuable insights into the reprogramming mechanism of monkey SCNT and introduce a promising strategy for primate cloning.